Micrometry of Liver of Non-descript Goats of Jammu Region in Different Age Groups - Sethi, Lovish; Suri, Shalini; Sarma, Kamal; Sasan, Jasvinder Singh (International Journal of Bio-resource and Stress Management, 2021)
The present study was conducted on the liver of non-descript goats of Jammu region during 2019. The samples were divided into young (below 1 year), adult (2–3 years) and senile (4 years and above) age groups as per the dentition. Six samples from each age group were collected. The capsule showed maximum thickness in adult age group. Maximum thickness of capsule was seen at upper part of main lobe (UPOML) in the liver of young, adult and senile age group. The diameter of central vein showed highest values in adult, followed senile group probably due to increased liver functions in adult. Inter-central vein distance was maximum in adult age group followed by young and senile groups. The mean values of length of hepatocytes ranged between 13.50 to 22.50 µm in all regions of liver of irrespective of age groups. The mean values showed higher values in adult and senile age groups. The nuclear diameter of the hepatocytes ranged between 9.00 to 13.50 µm with mean values varying between 9.75±0.50 to 10.50±0.64 µm in all the three age groups. Number of liver lobules per field was maximum at MPOML in senile group (14.16±0.61) whereas minimum number was observed at CL in young (4.41±0.22). Maximum number of portal triads per field was seen at VPOML in senile group (5.16±0.32) whereas minimum number was observed at VPOML in young group (3.08±0.19). In general, number of liver lobules and portal triads per field was highest in senile group followed by adult and young.